Balck economy in India - "Kabra, Kamal Nayan" (Delhi, 1982)
The postscript briefly updates the conceptual, theoretical and policy analyses which overviews how vast dramatic depravities grip India's democracy, development and human rights record in the direction of mal-development, plummeting the social existence of the masses to new lows of inhuman inequalities and indignities. It has been contributed to in no small measure by the transformation of the black economy into the grey political economy commanded in complicit ways by the miniscule minority of the rich and powerful sitting atop India's patrimonial corporate business empires in crony relationships with increasingly corporatized party high commands.
Keywords: India - economic policy